A case of acute abdomen caused by visceral disseminated varicella-zoster virus infection causes diagnostic challenges during the course of systemic lupus erythematosus - Koki Matsushita; Yu Nagayoshi; Ryosuke Yamamura; Keishi Nakamura; Yutaka Kakizoe; Yuichiro Izumi; Masataka Adachi; Masashi Mukoyama; Hideki Yokoi (IDCases, 2025)
Visceral disseminated varicella-zoster virus (VD-VZV) infection, resulting from primary infection by, or reactivation of, VZV, is a rare and severe complication in immunosuppressed patients. Because VD-VZV often develops alongside acute abdominal pain, which precedes appearance of the skin rash, diagnosis is difficult. Here, we report a case of 48-year-old woman who presented with acute abdomen, leading to a diagnosis of VD-VZV infection. The patient developed systemic lupus erythematosus 4 months earlier, and had been treated with immunosuppressants. The patient was treated successfully with a 7-day course of intravenous acyclovir. VD-VZV infection should be considered as a differential diagnosis in immunosuppressed patients with acute abdomen. Early diagnosis and prompt treatment with antivirals are crucial for improved patient outcomes.